The Moderate Islamic Education in Millennial Society (Analysis Study of Kh. Anwar Zahid's Sermon) - Assajad, Abdul Malik Fajar; Yenuri, Ali Ahmad (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This study aims to analyze KH. Anwar Zahid's lecture in conveying the concept of Islamic moderation in his lecture to the millennial community. The focus of this study includes identifying the values ​​of Islamic moderation, analyzing the lecture methods used, and evaluating their influence on the mindset and religious attitudes of the millennial generation. This study applies a descriptive qualitative method by analyzing the content of KH. Anwar Zahid's lecture which discusses Islamic moderation. Data collection was carried out through documentation studies and analyzed in order to understand the content of the message, delivery techniques, and its impact on the millennial community. The results of the study show that KH. Anwar Zahid conveys Islamic moderation in a light and easy-to-understand way. He uses humor and simple language, so that the concepts of moderation are more easily accepted by the millennial community. His lectures encourage balance, tolerance, and avoid extreme attitudes.